PENERAPAN METODE BIOKLIMATIK DALAM DESAIN RUSUNAMI YANG INTERAKTIF, SEHAT DAN AKTIF - Clairine Aloysia Benedicta; Sidhi Wiguna Teh (Jurusan Arsitektur dan Perencanaan, 2021)
Jakarta is one of the fastest growing areas in terms of population. The city of Jakarta as the capital city of the Republic of Indonesia has very rapid development and progress in various fields and sectors such as social, economic, cultural and political. Due to the attractiveness of Jakarta, it triggers urbanization which causes the number and density of Jakarta's population to continue to increase every year. With the increase in population, the need for housing also increases. Flats are one solution to the problem of population growth. Flats are considered to be the answer to the housing needs in urban areas, especially for the lower middle class. This study uses the “Bioclimatic Architecture” method as a design approach that refers to the design of buildings and spaces (interior - exterior - outdoor) based on the local climate, which aims to provide thermal and visual comfort, utilizing solar energy and other environmental sources. The basic element of the Bioclimatic Architectural design is Passive Solar Systems which are incorporated into the building and utilize environmental sources (eg sun, air, wind, vegetation, water, soil, sky) for heating, cooling and lighting of the building. The application of the bioclimatic method on rusunami aims to be a solution to ecological problems and the effectiveness of the use of materials with the aim of improving the quality of life of residents and making an interactive, healthy and active environment by optimizing natural elements and the application of appropriate spatial programs is expected to be useful for use. Keywords: Bioclimatic Architecture; Flats; Social; WellnessAbstrakJakarta merupakan salah satu wilayah yang pesat dalam hal kependudukan. Kota Jakarta sebagai Ibu Kota Negara Republik Indonesia memiliki perkembangan dan kemajuan yang sangat pesat di berbagai bidang dan sektor seperti sosial, ekonomi, budaya dan politik. Karena daya tarik yang ditimbulkan oleh Jakarta, hal tersebut memicu urbanisasi yang menyebabkan jumlah dan kepadatan penduduk Jakarta terus meningkat setiap tahunnya. Dengan adanya peningkatan jumlah penduduk maka kebutuhan akan hunian juga meningkat. Rumah susun menjadi salah satu solusi untuk menjawab permasalahan pertumbuhan populasi itu. Rumah Susun dianggap menjadi jawaban bagi kebutuhan pemukiman di wilayah perkotaan, khususnya bagi masyarakat menengah ke bawah. Studi ini menggunakan metode “Arsitektur Bioklimatik” sebagai pendekatan desain perancangan yang mengacu pada desain bangunan dan ruang (interior - eksterior - luar ruangan) berdasarkan iklim lokal, yang bertujuan untuk memberikan kenyamanan termal dan visual, memanfaatkan energi matahari dan sumber lingkungan lainnya. Elemen dasar dari desain Arsitektur Bioklimatik adalah sistem Passive Solar Systems yang dimasukkan ke dalam bangunan dan memanfaatkan sumber lingkungan (misalnya matahari, udara, angin, vegetasi, air, tanah, langit) untuk pemanas, pendingin dan penerangan bangunan. Penerapan metode bioklimatik pada rusunami bertujuan untuk menjadi solusi untuk permasalahan ekologi dan efektivitas penggunaan material dengan tujuan meningkatkan kualitas hidup warga dan menjadikan lingkungan yang interaktif, sehat dan aktif dengan mengoptimalkan unsur alam dan penerapan program ruang yang tepat diharapkan dapat bermanfaat untuk digunakan.